2017
DOI: 10.5606/archrheumatol.2017.5960
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Citrullinated Cyclic Peptide Antibody and Functional Disability Are Associated With Poor Sleep Quality in Rheumatoid Arthritis

Abstract: Objectives: This study aims to determine the predictors of poor sleep quality in rheumatoid arthritis (RA). Patients and methods:This was a monocentric, cross sectional, case-control study which was conducted at the Putrajaya Hospital, Malaysia. We recruited 46 patients with RA (3 males; 43 females; mean age 48.15±14.96) and 46 age and sex-matched healthy controls (3 males; 43 females; mean age 47.11±12.22). RA patients were assessed for their disease activity based on disease activity score in 28 joints, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We used serum CPR and SDAI scores as indices of inflammatory status and found serum CRP significantly influenced sleep disturbance and that SDAI did not. However, previous studies have reported SDAI significantly predicts sleep disturbance in RA patients (Fragiadaki et al, 2012; Rajalingam et al, 2017; Sariyildiz et al, 2014; Son et al, 2015; Westhovens et al, 2014). Further studies are needed to explain this discrepancy and to clarify the relationship between inflammatory status and sleep disturbance.…”
Section: Discussionmentioning
confidence: 79%
“…We used serum CPR and SDAI scores as indices of inflammatory status and found serum CRP significantly influenced sleep disturbance and that SDAI did not. However, previous studies have reported SDAI significantly predicts sleep disturbance in RA patients (Fragiadaki et al, 2012; Rajalingam et al, 2017; Sariyildiz et al, 2014; Son et al, 2015; Westhovens et al, 2014). Further studies are needed to explain this discrepancy and to clarify the relationship between inflammatory status and sleep disturbance.…”
Section: Discussionmentioning
confidence: 79%